Children With Epilepsy in Africa: Recommendations From the International Child Neurology Association/African Child Neurology Association Workshop. (May 2013) - Wilmshurst, Jo M.; Cross, J. Helen; Newton, Charles; Kakooza, Angelina M.; Wammanda, Robinson D.; Mallewa, Macpherson; Samia, Pauline; Venter, Andre; Hirtz, Deborah; Chugani, Harry
This article presents key findings from the International Child Neurology Association/African Child Neurology Association Workshop. The viability of international guidelines for the management of children with epilepsy should be reviewed within each African country, and adapted to comply with the regional capacity. Such recommendations can be used to lobby for resources. More training centers should be developed in Africa, so that specialists can be trained within Africa, in skills relevant to the continent, in collaboration with "out of Africa" visiting-specialists to develop the concept of "train the trainers." At least 1 child neurology specialist per 100 000 of the population is required. Specific to Africa are the challenges from stigma, prejudice, and misconceptions. "Epilepsy teams, " inclusive of the traditional healers, would enable management of increased numbers of children, and challenge policy such that it is the right of the child with epilepsy to have reliable access to appropriate antiepileptic drugs, support, and health care equity between the rural and urban settings.